Penerapan PPh 21 pada Freelance dan Pekerja Digital: Tantangan di Era Big Economy - Ani, Adinda Putri (Journal of Culture Accounting and Auditing, 2025)
The rise in the number of freelance and digital workers in the gig economy era presents new challenges in the application of Article 21 Income Tax (PPh 21). The traditional taxation system, designed for conventional employment, often does not align with the characteristics of freelance income, which tends to be fluctuating, irregular, and based on short-term contracts. This article aims to analyze the main challenges faced in implementing PPh 21 for freelance and digital workers and offers strategic solutions to optimize tax compliance in this sector. Using a descriptive-analytical approach, this study examines the technical, legal, and administrative aspects that serve as primary obstacles, including the lack of taxpayer education, the complexity of tax reporting, and the limited specific guidance in tax regulations. The article also explores the potential of digital technologies, such as tax reporting applications, as solutions to enhance efficiency and ease of reporting. The findings of this study are expected to contribute to policymakers in formulating more inclusive and adaptive regulations, while also providing practical guidance for freelance workers in fulfilling their tax obligations.